WORKPLACE FACTORS AND PERFORMANCE OUTCOMES: A CASE STUDY OF DISCIPLINE AND ENVIRONMENT AT AN INDONESIAN PORT COMPANY - Hepiana Patmarina; Khoiru Kalam (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the influence of work discipline and the work environment on employee performance at PT. Pelabuhan Bukit Prima Tarahan, a strategic port company in Lampung. Using a quantitative approach with a causal design, the study involved all 33 employees as respondents (census). Primary data was collected through a closed-ended questionnaire using a 1-5 Likert scale, which was tested for validity and reliability. Data analysis employed multiple linear regression. The results show that: (1) Work discipline has a positive and significant effect on employee performance; (2) The work environment has a positive and significant effect on employee performance; and (3) Work discipline and the work environment simultaneously have a positive and significant effect on employee performance. The regression model explains 66.2% of the variation in performance (Adjusted R² = 0.662). These findings support Herzberg's Two-Factor Theory, confirming that work discipline as a motivator factor and the work environment as a hygiene factor are together crucial prerequisites for optimal performance in the challenging context of port operations. This study provides an empirical contribution to the HR management literature in the maritime sector and practical recommendations for management to adopt integrated strategies that strengthen discipline and improve the work environment.